Evaluating the clinical application of PAMD score in assessment of TRUS-biopsy positive outcomes in patients with PSA 4-10 ng/ml treated in Serbia. - Zubelić, Aleksa; Radovanović, Milan (Medical Research, 2023)
Introduction: Transrectal ultrasound guided prostate biopsy (TRUS-biopsy) is the "gold standard" in the diagnosis of prostate cancer (PC). There are divided opinions about the need for biopsy in patients with prostate-specific antigen (PSA) between 4 and 10 ng/ml. The positive biopsy outcome (PC) in these patients ranges between 20-39%. The low sensitivity and specificity of PSA in predicting positive biopsy outcome results in large number of unnecessary biopsies and treatments. In order to better select candidates for biopsy, several risk stratification models for PC have been proposed in recent years, among them the PAMD score.Aim: The aim of this study was to examine the value of the PAMD score in the assessment of positive biopsy outcomes in our population of patients, as well as to examine individual risk factors for PC in patients with PSA values between 4 and 10 ng/ml treated in Serbia.  Material and methods: The study involved 50 patients from Clinic of Urology, University Clinical Centre of Serbia, whose PSA value were measured in the range of 4-10 ng/ml. In all patients we measured PSA and %fPSA, and performed DRE, as well as magnetic resonance imaging (MRI) to evaluate prostate volume (PV) and PI-RADS score. All patients underwent TRUS-guided systemic prostate biopsy. In accordance with the data from literature, PAMD score was determined for all patients.Results: A PAMD score > 3 showed a high specificity in the prediction of PC, as well as an association with a higher frequency of high-grade PC. A positive finding on DRE, %fPSA < 16, age higher than 69 years and PI-RADS > 3 showed a statistically significant association with the existence of PC. A high individual predictive value in assessing the presence of PC was confirmed for DRE, %fPSA, PV, and PI-RADS score.Conclusion: The PAMD scoring system may be of importance in the better selection of candidates for TRUS-biopsy, in population of patients with PSA values 4-10 ng/ml.
Keywords: prostate cancer, PSA, PAMD, risk factors.